TARIFF PROTECTION POLICIES OF MAJOR AGRICULTURAL CROPS IN IRAN - Y. Feizabadi (Journal of Animal and Plant Sciences, 2015)
Iran`s Agricultural sector is characterized by high tariffs which appear consistent with its political economy equilibrium. To assess tariff structure of agricultural sector, we need to understand what determines that structure. In this article, tariff equation of agricultural sector has been estimated for 100 selected agricultural crops using OLS method. Political variables, as independent variables in tariff equation, include concentration index, Import/output ratio, Intra-industry trade, degree of processing and wage. The overall fit of the equation is acceptable and variables tend to have the expected signs, at high significance level. Afterwards, political optimum tariff and political protection indicator are estimated for all intended products. This political-economy analysis allows us to identify two sets of protected products. First, over-protected products (most of fully- processed products) are those which their actual tariffs are higher than their political optimum tariffs (the value predicted by the political economy variables described). Tariff reduction should not be politically costly. Then, tariff cuts could be more speedy. Second, under-protected products (most of first stage products) are those which their actual tariffs are lower than their political optimum tariffs. Tariff reduction will be politically costly and longer adjusted period may be necessary. In both cases tariff reductions would improve resources allocation and efficiency within the agricultural sector. Therefore, Iranian authorities should consider speeding up long term tariff cuts to provide effective levels of protection.
Keywords: Agricultural Sector; Tariff Protection; Over and Under-protected Products; Political Protection Indicator